Automation systems in automatic assembling gear shaft output as car gearbox part at PT. Matahari Megah. Issue 1 (December 2020) - Raynaldo, Kevin; Darmawan, Steven; Halim, Agus; Nugroho, Asih
Abstract: This study is an observation and analysis about automatic assembling gear shaft output as car gearbox part that made at PT. Matahari Megah as a result of research. That automation product can reduce the assembly time from about 5 minutes to less than 45 seconds. Then the objectives in this case study are to describe assembly processes, how to choose censoring systems properly, and give recommendation in calculating compressive force for servo press mechanism. Automatic assembling gear shaft output has four main assembly stations consists of station OP 10, OP 20, OP 30, and OP 40. One of the most important element at that product is censoring system mounted at station check for checking the workpiece properly. The recommendations given are about the acrylic plate mounted at station check to reduce the amount of photoelectric sensor and equation for calculating compressive force for pressing gear and bearing to the output shaft appropriately.